Assessment of Fruit Drop in Different Cultivars of Litchi - Narayan Lal; Abhay Kumar; E. S. Marboh; Vishal Nath; S. D. Pandey (International Journal of Economic Plants)
Individual panicles produce hundreds of pistillate flowers but only a small proportion of these bear fruit and reach maturity. There are some stages of fruit drop during growth and development caused by different factors. An experimental trial was conducted in National Active Germplasm Site (NAGS) at ICAR-NRC on Litchi, Muzaffarpur, to assess the fruit drop due to different factors during 2014–2015. The result revealed that four factors viz., improper pollination and fertilization, embryo abortion, seed and fruit borer, and normal fruit abscission were associated with fruit drop in litchi and fruit drop varied from 23.53–77.54% with a maximum in Shahi and lowest in Elaichi during the first week of flowering. Fruit drop increased to 92.65–97.86% during the third week of flowering because of improper pollination and fertilization, and it reached a maximum level of 98.51–99.70% at the time of ripening stage with the lowest in Deshi. Embryo abortion was one primary cause of fruit drop during the 4th week whereas infestation of seed and fruit borer was the major factor for fruit drop during the 5–7th week. Such fruit drop can be controlled by managing the infestation of borer. Abscission due to ethylene production and heat stress during the maturity of fruit was yet another cause of fruit drop. This study will help to researcher to find out the time of infestation of seed and fruit borer which causes heavy fruit drop and it can be controlled with pest management option.